Eurozone Debt Crisis and Albania - Guga, Irma (European Scientific Journal, ESJ, 2019)
Albania as part of the Western Balkans was affected by the consequences of the financial crisis in 2009 followed by the EU debt crisis. However, as a result of external factors, the slowdown in economic growth began to feel in 2008. Despite the fact that the economic growth in the country was the largest in the Western Balkans region and remained at positive levels even during the crisis, some of the economic and financial indicators had significant impact. Also, high increase in public spending in the infrastructure area was noticed, which accompanied the pre-crisis period and further deteriorated by its impact. Looking at these up rising data of the budget deficit and the public debt to cover the latter, IMF proposed two fiscal rules in order to contribute strengthening fiscal sustainability: 1- The debt rule, which directly allows the full functioning of automatic stabilizers and keeps government under control; 2- The expenditure rule aiming at debt brake, which allows a close connection between the operational goal and the fiscal sustainability objective (IMF Country Report No. 10/206: July 2010). Focus of this paper is particularly on the most important economic and financial indicators in Albania to better understand the extent of the impact of this crisis in the country and the measures taken as well. Through the comparisons of the situation before and after the crisis will be reached on the conclusions on the main instruments used by the government to cope with the crisis or avoid its consequences.